The Legal Status of the National Data Protection Authority in light of the Regulatory State Theory: Is there any room for the adoption of the material concept of administrative decentralization in Brazil? - Antunes Lima da Fonseca Carvalho, João Pedro (Law, State and Telecommunications Review, 2020)
Purpose ”“ The purpose of this paper is to investigate the adequacy of the legal nature of the National Data Protection Authority (ANPD), proposed by Law no. 13.853/19, to the reality of Brazilian Law, starting from the theoretical bases developed by the Regulatory State Theory regarding the valorization of the technical decision immune to political influences. Methodology ”“ This study adopts the doctrine revision of the Regulatory State Theory, aiming to point the theoretical bases on the autonomy of the regulatory entities, in order to make the comparison of adequacy between the legal nature of the ANPD placed in Law no. 13.709/18 and the material concept of administrative decentralization. Findings ”“ The study demonstrates that the Brazilian legal-political tradition will make it difficult for the National Data Protection Supervisor to act in view of its legal nature as a public body that is part of the structure of the Presidency of the Republic, which greatly relativizes its autonomy. Practical Implications ”“ The probable revision of the legal nature of the ANPD, as provided for in art. 55-A, §1, of Law no. 13.709/18, and the effectiveness of the performance of this National Authority. Originality ”“ A very current issue in the Brazilian legal environment is the suitability of the companies that will be affected by the entry into force of the General Data Protection Act (Law no. 13.709/18) in August 2020, due to the comprehensive potential of this law. This paper studies the legal nature of the National Data Protection Authority, a regulatory body that will have a relevant regulatory role in the data economy society, highlighting the relevance of the study to the sector.